Abordagem molecular da neuropatia auditiva - Silva, Magali Aparecida Menezes da (2015)
Introduction: Mutations in the otoferlin gene (OTOF) can account for Auditory Neuropathy. Objective: To investigate the prevalence of mutations in OTOF gene in patients with and without Auditory Neuropathy. Casuistic and Methods: This original cross-sectional study evaluated 16 index cases with auditory neuropathy; 13 patients with sensorineural hearing loss and 20 normal-hearing subjects. DNA was extracted from peripheral blood leukocytes, and the OTOF gene sites were amplified by PCR-RFLP. Results: Out of the 16 index cases, 9 (56%) are female and 7 (44%) are male. Out of the 13 deaf patients, 7 (54%) are male and 6 (46%) female. Among the 20 listeners, 13 (65%) are male and 7 (35%) female. Thirteen (81%) index cases had wild-type genotype (AA) and 3 (19%), had the heterozygous AG genotype for IVS8-2A-G (intron 8) mutation. The 5473C-G (exon 44) mutation was found in a heterozygous state (CG) in 7 (44%) index cases and 9 (56%) had the wild-type allele (CC). Of these mutants, two (25%) are compound heterozygote for the mutations found in intron 8 and exon 44. All patients (100%) with hearing loss and listeners do not have mutations. Conclusion: Differences at the molecular level are found in patients with and without Auditory Neuropathy.